Survey of Intentional Enterprises Threats using Social Engineering Exploits and Prevention Techniques (International Journal of Engineering and Computer Science, 2017)
this is a survey report of social Engineering threats that include various phases of social engineering. As security techniques increase, security break techniques will also increase in the same or more ratios. In this paper, we are trying to cover most areas of social engineering feats with Cause of social engineering in enterprises, various techniques of social engineering, influences and popular social engineering cases with relative study​.